THE PORTRAIT OF MEMORY AND OBLIVION. CONCILIATION POLICIES, FORGETFULNESS AND EMBLEMATIC MEMORIES OF THE FEDERICO TINOCO GRANADOS DICTATORSHIP (1917-1963) - Bonilla Castro, Alejandro (2014)
The main objective of this paper is the analysis of the emblematic memories created by the tinoquistas, the revolutionary groups and the urban workers about the Federico Tinoco Granados dictatorship (1917-1919) and the democratic transition – known as the Process of Restoration (1920-1926). The focus of the analysis will be the battle of those memories in the media, the public spaces in the capital city San José, the Costa Rican government’s institutions and the long term effect of the conciliation policies, applied by the Presidents Julio Acosta García and Ricardo Jiménez Oreamuno, to put an end to the inner political and social conflict in the country after the dictatorship and to erase whichever expression of the emblematic memories after 1927.